Hubungan penurunan aktivitas fisik dengan Saturasi oksigen pada lanjut usia Di posyandu makamhaji - Widhisusanti, Nita, Sugiono, S.Fis, MH.Kes (2016)
Background: Decreased physical activity is found mainly in elderly people causing problems in society. It may happen because less efforts of maintaining physical fitness in older ages. Aging is related to degenerative changes of skin, blood vessels, bones, hearts, nerves and other body tissues. One of blood vessel problems is indicated by reduced oxygen level of blood called oxygen saturation. Purpose of the Research: The research seeks to know relationship between decreased physical activity and oxygen saturation in elderly people of Posyandu Makamhaji. Benefits of the Research: The research aims to know correlation between the decreased physical activity and oxygen saturation in elderly people of Posyandu Makamhaji. Method of the Research: The research is observational one with cross-sectional approach. Sample was taken by using purposive sampling amounting to 65 respondents. Oxygen saturation was measured by using Pulse Oxymetri with inclusive sample. Correlation was examined by using Chi-Square. Results of the Research: Based on results of Chi-Square statistical test, it can be seen that p-value of 0.217 < 0.005. It can be interpreted that no correlation is found between decreased physical activity and oxygen saturation in elderly people of Posyandu Makamhaji. Conclusion: There is no correlation between decreased physical activity and oxygen saturation in elderly people of Posyandu Makamhaji.